Efavirenz induced drug hypersensitivity reaction - Bandyopadhyay, Arkapal; Chaurasia, Rakesh Chandra; Yadav, Rakesh Kumar; Palepu, Sarika (International Journal of Advances in Medicine, 2018)
Efavirenz is the first line non-nucleoside reverse transcriptase inhibitor suggested by World Health Organization for newly diagnosed patients started on antiretroviral therapy. Dermatologic manifestations are the usual side effects associated with this drug. Authors hereby, present a case report of efavirenz induced drug hypersensitivity reported at a tertiary care hospital at Allahabad, Uttar Pradesh. The patient developed rashes and vomiting within a week of start of TLE regimen. Re-challenge test revealed confirmation of the adverse drug reaction by efavirenz. Change of the regimen was done for the patient following hospitalization for the event. This case report explains that strict pharmacovigilance is essential in the initial days of start of antiretroviral therapy. Further trials to improve the safety profile of the patients on ART are the need of the hour.